Analisis Desain Sistem Informasi Terintegrasi dan User Interface pada Sistem Informasi Sekolah (SISKO) di Perpustakaan SMA Negeri 1 Yogyakarta - Nurwidianto Yuli Saputra; Syifaun Nafisah (Pustabiblia: Journal of Library and Information Science, 2020)
SISKO was developed since 2005 in SMA Negeri 1 Yogyakarta through the assistance of Kamadeva developer under the auspices of PT. Indonesia Mandiri. The interesting side of this research is SISKO as an integrated information system between the school administration module and the Library, SISKO will be reviewed from the analysis of its library information system design. The research method through a descriptive qualitative research approached, namely by conducted field observation techniques, direct interviews and collected available data. Based on the results of the information system design analysts showed the relationship between data or entities with each other. The focus of the analysis of the design of the library information system at SISKO also showed the detailed process flow especially in circulation services at SMA Negeri 1 Yogyakarta Library. SISKO viewed from the back end through its user interface can run well.